The influence of plant components on microbiological and oxidative processes in dry fish and plant products during storage - S. V. Zolotokopova; I. Koroma; A. A. Nevalennaya; E. Y. Lebedeva (Новые технологии, 2024)
A pressing issue in the food industry is providing the population with adequate nutrition. According to the concept of healthy eating, a person needs to increase the consumption of plant foods without reducing the consumption of foods containing complete protein. We have created dry fish and plant products, in the form of food concentrates, containing all the necessary macro- and micronutrients. The purpose of the research was to study the influence of plant components on the microbiological and oxidative processes of dry fish and fish-plant products during storage. To achieve the intended goal, the tasks of determining microbiological indicators and oxidation products at the beginning and end of the storage period were solved. Storage of dry fish and plant products was carried out for 12 months in polymer packaging at a temperature of plus 20±5℃. All analyses were carried out using generally accepted standard methods. As a result of the studies, it was established that the microbiological indicators of a dry fish-plant product, due to the addition of vegetables and corn flour, were higher than those of a dry fish product (0.5x104 and 0.2x104 CFU per 1 g, respectively), but during storage the bacterial contamination of dry of fish and plant products decreased from 0.5x104 to 0.1x104 CFU per 1 g of product. Also, plant components affected the oxidative processes in dry fish and vegetable products. The acid number in samples of dry fish product increased from 0.71 to 2.67 mg of KOH, and in samples of dry fish-plant product – from 0.65 to 1.87 mg of KOH after 12 months of storage. Thus, plant components inhibited the oxidation process and maintain the quality of the product during storage.